Perubahan Guna Lahan dan Kebutuhan Ruang Parkir di Jalan Pengayoman, Kota Makassar - Ibrahim Subiar; Ananto Yudono; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2016)
Changes in land use certainly have an impact on changing the demand for parking spaces of each type of land use that exists from year to year. The purpose of this study is to identify changes in land use in this case the floor area and building functions that occur within a certain time span (2001-2014) and predictions in 2034, and to determine the impact of these changes on the needs of parking spaces on Jalan Pengayoman Makassar. The analytical methods used to determine land use changes every year are spatial analysis and map drawings, simple regression analysis to predict land use changes in 2034 and standard suitability analysis to determine parking space requirements in the study area. The results showed that since 2001-2014 the type of land use for houses and vacant land has decreased the amount of floor area. This is inversely proportional to other types of land use such as shops, shop houses, services, and offices which tend to increase in building floor area including predictions for use in 2034. Functional changes in buildings that occurred in the period 2001-2014 are houses and vacant land that tends to change to trade and service functions. This is caused by the presence of vulnerable economic growth that occurred in Makassar City in 2001-2012. Changes in land use have an impact on changing parking space requirements for each type of land use that exists from year to year, especially for trade and service functions.